Curvas com modelos canônicos em scrolls - Danielle Franco Nicolau Lara (2014)
Let C be an integral and projective curve whose canonical model C lies on a rational normal scroll S of dimension n. We mainly study some properties on C, such as gonality and the kind of singularities, in the case where n = 2 and C is non-Gorenstein, and in the case where n = 3, the scroll S is smooth, and C is a set theoretic complete intersection inside S. We also prove that a rational monomial curve with just one singular point lies on a surface scroll iff its gonality is at most 3, and that it lies on a threefold scroll iff its gonality is at most 4.